Children's right to participate in early childhood education settings: a systematic review - Correia, N. (2019)
Children's right to participate is considered pivotal for establishing a culture of democracy and citizenship. Although this is not a new concept, its application remains a challenge. This review aims to map peer-reviewed empirical research conducted on children's right to participate, in center-based early childhood education settings, from 1980 on. A systematic literature search was performed and 36 studies met the inclusion criteria. Findings suggest a limited number of publications, conducted mostly in northern Europe countries, in the education field. Regarding definitions and theoretical backgrounds, sociological, legal, democratic, and educational discourses converge. There is a prominence of qualitative studies, a greater focus of research on ideas about participation, and, to a lesser extent, a focus on practices to promote participation. There is more emphasis on teacher's perspectives and practices, with few studies relying on children as informants, and limited sound measures to assess children's participation. Future research should rely on multiple informants, and investigate associations between this right and children's individual outcomes.